Increase of tourist traffic on Spitsbergen: An environmental challenge or chance for progress in the region? - Kugiejko, Magdalena (Polish Polar Research, 2021)
The Arctic region is under considerable pressure from the rapidly growing global tourism industry. The goal of this article is to present the current state of tourism in Spitsbergen, including the results of empirical research about the type of tourists and their preferences in organizing a trip, i.e. motivation, choice of attractions, etc. The survey in Longyearbyen town was conducted in 2018 and 2019 during two summer and two winter trips. As a result, a total of n=214 questionnaires were collected, presenting interesting insights into tourists’ profiles and their motivation in coming to the island. Based on the results, the Arctic tourism sector is characterized by seasonality, which significantly affects the distribution of tourist arrivals throughout the year. During the last 15 years, Spitsbergen island noticed the greatest boom in tourism linked to the development of transport infrastructure (new ports and airports) and accommodation (hotels). From one side, the tourism industry contributes significantly to employment in Longyearbyen, still from the other side, it burdens the local community and challenges their lives due to increased pollution of air, water and ground. The increased tourism also poses serious threats to the natural environment, which is already under pressure due to global warming resulting in melting Arctic glaciers and increased sea level. Therefore, it is crucial to implement new regulations to control and manage the development of tourism while protecting nature and its residents.